2014
DOI: 10.1097/01.mib.0000441201.10454.06
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ATP-activated P2X7 Receptors in the Intestinal Mucosa Is Implicated in the Pathogenesis of Crohnʼs Disease

Abstract: The upregulation of P2X7-R in CD inflamed mucosa is consistent with the involvement of purinoceptors in inflammation and apoptosis. These observations may implicate purinergic signaling in the pathogenesis of intestinal inflammation, and the P2X7-R may represent a novel therapeutic target in CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 73 publications
6
70
0
6
Order By: Relevance
“…Using a mouse model of acute AOM/DSS-induced colonic inflammation, we found that P2rx7 À/À mice displayed reduced signs of inflammation. This finding is in agreement with recent studies demonstrating that prophylactic systemic blockade of the P2RX7 activity prevented TNBS-induced colitis in rats (12) and that overexpression of P2RX7 in the intestinal mucosa was associated with the pathogenesis of CD (34). In the current study, we found that P2RX7 inactivation using selective antagonists as well as genetic deletion of the P2rx7 gene attenuated the weight loss and the overall disease activity score (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Using a mouse model of acute AOM/DSS-induced colonic inflammation, we found that P2rx7 À/À mice displayed reduced signs of inflammation. This finding is in agreement with recent studies demonstrating that prophylactic systemic blockade of the P2RX7 activity prevented TNBS-induced colitis in rats (12) and that overexpression of P2RX7 in the intestinal mucosa was associated with the pathogenesis of CD (34). In the current study, we found that P2RX7 inactivation using selective antagonists as well as genetic deletion of the P2rx7 gene attenuated the weight loss and the overall disease activity score (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, recent findings suggest that commensal bacteria are the major source of eATP in the intestinal lumen. Furthermore, patients with CD have increased numbers of mucosa-associated adhesive E. coli [72]; direct purinergic communication between those bacteria and epithelial cells may lead to eATP-mediated mucosal inflammation. In the future, molecular imaging might be used to precisely elucidate the trafficking of ATP that is released into the luminal and mucosal inflammatory compartments in patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings show that eATP disrupts the regulatory–inflammatory T-cell balance in the intestinal compartment and initiates intestinal inflammation. Data from both mouse and human studies suggest eATP/P2X7R pathways as promising therapeutic targets for overcoming IBD, and clinical trials for validation of therapeutic targets should be conducted in the future [72,73,74]. …”
Section: Eatp As An Inflammatory Mediator In Intestinal Inflammationmentioning
confidence: 99%
“…Regarding the signaling through purinergic receptors, the P2X7R was shown to play a role in the development of both innate and adaptive Th17 immune responses in skin and intestinal lamina propria (35,36,73). We previously showed that the purinergic signaling pathway was upregulated in VAT of MUO patients, and that it could chronically maintain the inflammasome activity and IL-1b production in tissue (43).…”
Section: Discussionmentioning
confidence: 99%